A Comparative Analysis of Project-Based Learning (PBL) and Traditional Laboratory Methods in Teaching Toxicology - Maksud Ravshanov, Shakhlo, Abdurakhmonova, Marjona Boyirova, Dilbar Ubaydullaeva (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article presents a comparative analysis of two key pedagogical methods for teaching toxicology in higher education: traditional laboratory exercises and Project-Based Learning (PBL). The study aims to evaluate the effectiveness of each method in improving students' theoretical knowledge of toxins, developing practical analytical skills, and fostering critical thinking and case-based reasoning. The research involved two groups of pharmacy students: one group performed traditional, instruction-based experiments for toxin identification, while the other engaged in a project centered on a simulated real-world poisoning scenario. Outcomes were assessed through pre- and post-tests, analysis of case reports, and student feedback surveys. The findings indicate that the PBL method offers significant advantages in enhancing student engagement, intrinsic motivation, and the development of higher-order cognitive skills, such as diagnostic reasoning and risk assessment. Conversely, the traditional method proved highly effective for mastering specific, standardized analytical techniques. The article analyzes the strengths and weaknesses of both methods and provides recommendations for implementing an integrated (hybrid) approach to teaching the complex and case-sensitive subject of toxicology.